The effect of solution heat treatment on the tensile and creep properties of MarM-002 - Ming, Vin Ree (Centre for Materials Engineering, 2016)
The nickel-base superalloy MarM-002 is a high strength precipitation hardening material used in structural applications in the gas turbine field. The microstructure of MarM-002 consists of fine y' precipitates, a y matrix, carbides and a eutectic y- y' where the y' can be composed of coarse lamellae or blocky y' precipitates. Increasing the volume fraction of fine y' by dissolving the coarse eutectic y' during solution treatment can raise the alloy strength. In practice the solution heat treatment temperature does not usually exceed 1220°C because of the danger of incipient melting. At 1220°c the eutectic y' does not dissolve and persists in the alloy structure. In the current project an alternative solution treatment technique, the varied rate solution heat treatment (VRSHT), was determined specifically for MarM-002, and was used to achieve higher solution treatment temperatures up to 1260°C without incipient melting. The microstructural response of MarM-002 to the conventional 1220°C solution heat treatment, and to solution treatment at temperatures above 1220°C, was studied extensively. Microstructural features such as carbide decomposition and the degree of y' and eutectic y' dissolution were noted. The tantalum and titanium rich carbides which form during casting were seen to decompose during solution treatment, while hafnium rich carbides precipitated in the interdendritic regions during heat treatment. The y' solvus and eutectic y' solvus was measured to be1260°C and 1280°C respectively. A 1050°C/12h +_ 870°C/16h ageing heat treatment was applied to the alloy following solution treatment and the effect on the y' characteristics was also studied.